The effects of wearing lower-body compression garments during endurance cycling - Scanlan, A. T.; Dascombe, B. J.; Reaburn, P. R. J.; Osborne, M. (International Journal of Sports Physiology and Performance, 2008)
Purpose: The present investigation examined the physiological and performance effects of lower-body compression garments (LBCG) during a one-hour cycling time-trial in well-trained cyclists. Methods: Twelve well-trained male cyclists ([mean ± SD] age: 20.5 ± 3.6 years; height: 177.5 ± 4.9 cm; body mass: 70.5 ± 7.5 kg; VO2max: 55.2 ± 6.8 mL·kg-1·min-1) volunteered for the study. Each subject completed two randomly ordered stepwise incremental tests and two randomly ordered one-hour time trials (1HTT) wearing either full-length SportSkins Classic LBCG or underwear briefs (control). Blood lactate concentration ([BLa-]), heart rate (HR), oxygen consumption (VO2) and muscle oxygenation (mOxy) were recorded throughout each test. Indicators of cycling endurance performance were anaerobic threshold (AnT) and VO2max values from the incremental test, and mean power (W), peak power (W), and total work (kJ) from the 1HTT. Magnitude-based inferences were used to determine if LBCG demonstrated any performance and/or physiological benefits. Results: A likely practically significant increase (86%:12%:2%; eta2 = 0.6) in power output at AnT was observed in the LBCG condition (CONT: 245.9 ± 55.7 W; LBCG: 259.8 ± 44.6 W). Further, a possible practically significant improvement (78%:19%:3%; eta2 = 0.6) was reported in muscle oxygenation economy (W·%mOxy-1) across the 1HTT (mOxy: CONT: 52.2 ± 12.2%; LBCG: 57.3 ± 8.2%). Conclusions: The present results demonstrated limited physiological benefits and no performance enhancement through wearing LBCG during a cycling time trial.